Long‐term outcomes from prophylactic or episodic treatment of haemophilia A: A systematic review. Issue 5 (13th July 2018) - O'Hara, J.; Sima, C. S.; Frimpter, J.; Paliargues, F.; Chu, P.; Presch, I.
Abstract : Introduction: Evaluating treatment success in patients with haemophilia A (HA) remains a vigorous debate, especially concerning the interpretation of results from clinical and observational research. The benefits of short‐term prophylaxis are well established, but long‐term outcomes, particularly related to humanistic and economic burden, are not as well understood. Aim: We conducted a systematic literature review to evaluate the association of episodic or prophylactic bleed control with long‐term clinical, humanistic and economic outcomes. Methods: Studies published in English between 1 January 2006 and 15 December 2016 were included. Participants had HA (with or without inhibitors), received prophylactic or episodic treatment and had at least 4 years of treatment or follow‐up. Results were analysed qualitatively with descriptive findings. Results: A total of 2091 records were screened, resulting in 19 studies from 20 publications for inclusion. Most studies included children (84%), were limited to patients with severe disease (74%) and were conducted in Europe or North America (89%). Ten studies (53%) included patients with inhibitors. Median study follow‐up ranged from 5 to 19 years. Long‐term bleeding and haemarthrosis outcomes were consistently better for patients receiving prophylaxis, who also required fewer hospitalizations or surgeries. Health‐related quality of life, functionality and productivity were generally more favourable in patients receiving prophylaxis. Quantitative comparisons were not feasible due to the lack of consistency in endpoint collection and reporting among studies. Conclusion: This systematic review confirmed that the benefits of prophylactic treatment on short‐term outcomes translate to broader long‐term clinical, humanistic and economic benefits. Better harmonization of data collection and outcome assessments across both registries and clinical studies is needed to allow for effective comparisons across studies and across data sources.